Development of a novel training system for laparoscopic inguinal hernia repair. Issue 4 (4th July 2019) - Poudel, Saseem; Kurashima, Yo; Kawarada, Yo; Murakami, Yoshihiro; Tanaka, Kimitaka; Kawase, Hiroshi; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: Background: Laparoscopic inguinal hernia repair is considered technically difficult. Although a simulation-based curriculum has been developed to help trainees, access to simulation training outside North America is limited. This study aimed to develop an educational system for the transabdominal preperitoneal (TAPP) approach based on the TAPP checklist, an assessment tool we had developed and validated earlier. Material and methods: Consensus within the TAPP education working group consisting of local TAPP experts, hernia experts and a surgical educator to develop educational tools and the educational system based on the TAPP checklist. The system was piloted in several institutes, and participants were surveyed on its efficacy. Results: We systematically developed an educational video and training manual explaining each item of the TAPP checklist and conveying basic knowledge of the procedure. We integrated the training tool with evaluation and feedback to develop an educational system. In a pilot study, seven trainees at five hospitals were trained using this system and found it very useful for mastering the TAPP procedure. Conclusions: We have developed a training system for TAPP procedure and successfully implemented it in several hospitals. Further research will focus on the educational value of this tool.